The Urgency of Legal Protection For Child Victims of Economic Exploitation by Parents in Cirebon Regency - Saefulloh, Asep Aep; Juanda, Ferdy Adrian; Ramadhan, Galuh; Henda, Raden; Nurhaqi, Ari (PT FORMOSA CENDEKIA GLOBAL, 2025)
Economic exploitation of children by parents is a form of human rights violation that requires comprehensive legal protection. This study aims to assess the urgency of legal protection for child victims of economic exploitation in Cirebon Regency. Methods, Using a juridical-empirical approach. Various laws and regulations have guaranteed child protection, such as Law Number 35 of 2014 concerning child protection. However, the reality on the ground shows that there are still cases of child exploitation carried out by parents, especially in the Plered District. This finding was obtained from interviews with the Cirebon Regency social service and the direct perpetrators. The study's results show that even though regulations are in place, their implementation is still weak due to limited supervision and a lack of legal awareness among the public. Therefore, institutional strengthening and legal education are needed to prevent the economic exploitation of children more effectively.